Feasibility of using Source Code Changes on the Selection of Text-based Regression Test Cases - Araújo, Joelson; Araújo, Jaedson; Magalhães, Cláudio; Andrade, João; Mota, Alexandre (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2017: Anais do II Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2017)
This paper investigates the relationship between recently modified source code and the selection of text-based regression test cases. The main reason is that our industrial partner uses release notes documents to perform such a selection, but these documents are not so well-written as the text-based test cases. Therefore, we intend to extract useful text from source code to see whether they can serve as a source of keywords in the selection process. We present an experiment that shows promising results about this hypothesis.